UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN GAHARU (Aquilaria microcarpa Baill.) TERHADAP BAKTERI Salmonella typhi dan Bacillus subtilis SECARA IN VITRO - Rafika Sari; Frans Kristian; Inarah Fajriaty (Akademi Farmasi Yarsi Pontianak, 2021)
Infections caused by pathogens such as salmonella typhi and Bacillus subtilis causes gastrointestinal infections and lead researchers to found a material that has potential as an antibacterial that has optimal efficacy by using the leaves of agarwood (Aquilaria microcarpa Baill.). The purpose of this study was to determine the compound class of secondary metabolites and antibacterial activity against salmonella typhi and bacillus subtilis of ethanol extract of agarwood leaves. The method used in the maceration and antibacterial activity test was diffusion method (Kirby-Bauer). Result are the ethanol extract of the agarwood leaves contain the compound flavonoids, saponins, tannins, steroids, and the solubility extract in water and ethanol are 21,80 ± 1,77% and 22,86 ± 2,78%. Shrinkage drying 26,25 ± 1,03%. Specific gravity 1% ethanol extract 1,0120mg/ml. Based on the research results antibacterial activity with the concentration of extract 300mg/ml, 400mg/ml, 500mg/ml toward salmonella typhi with an average diameter of inhibition zone 11,74 ± 0,44 mm, 13,55 ± 0,30 mm, 14,69 ± 0,67 mm and Bacillus subtillis with an average diameter of inhibition zone 10,29 ± 0,16 mm, 12,23 ± 0,21 mm, 13,56 ± 0,66 mm. The conclution is 500mg/ml concentration had a better antibacterial activity.